EFEKTIVITAS BACK MASSAGE DENGAN MULLIGAN BENT LEG RAISE PADA INTERVENSI ULTRASOUND DALAM MENURUNKAN NYERI DAN DISABILITAS PADA MECHANICAL LOW BACK PAIN - Putu Ayu Sita Saraswati; Sayu Aryantari Putri Thanaya; Komang Embun Dini Hari (Majalah Ilmiah Fisioterapi Indonesia, 2021)
Mechanical Low Back Pain (LBP) is the result of poor posture which causes mechanical stress on the lower back. Data from Sanglah General Hospital in 2010 stated that of the 249 outpatient LBP patients, 26% -37% had a tendency to relapse, and 11% -12% had disabilities. LBP does not only have an impact on health, especially on musculoskeletal injuries, but it can give an impact on work and work productivity which it can have an impact on patient finances. Effective treatment for LBP can be a solution to patient complaints. Physiotherapists can provide treatments such as Ultrasound, Mulligan Bent Leg and Back Massage. This study was purpose to compare the effectiveness of the combination of Back Massage and Ultrasound with Mulligan Bent Leg Raise and Ultrasound in reducing pain and disability due to Mechanical LBP. The research method used was experimental randomized pre-test and post-test control group design. The results of this study were back massage intervention with ultrasound (p <0.001) and mulligan bent leg with ultrasound (p <0.001) can reduce disability and pain in patients with mechanical LBP, and Mulligan bent leg with ultrasound (p <0.001) proved to be more effective. compared back massage with ultrasound in reducing disability and pain in mechanical LBP patients. Keyword: Massage, Mulligan, Mechanical Low Back Pain, Pain, Disability